The Impact of T Cell Vaccination in Alleviating and Regulating Systemic Lupus Erythematosus Manifestation - Liuye Huang; Yuan Yang; Yu Kuang; Dapeng Wei; Wanyi Li; Qin Yin; Juan Pang; Zhongwei Zhang (Journal of Immunology Research)
Objective. Systemic lupus erythematosus (SLE) is an autoimmune disease identified by a plethora of production of autoantibodies. Autoreactive T cells may play an important role in the process. Attenuated T cell vaccination (TCV) has proven to benefit some autoimmune diseases by deleting or suppressing pathogenic T cells. However, clinical evidence for TCV in SLE is still limited. Therefore, this self-controlled study concentrates on the clinical effects of TCV on SLE patients. Methods. 16 patients were enrolled in the study; they accepted TCV regularly. SLEDAI, clinical symptoms, blood parameters including complements 3 and 4 levels, ANA, and anti-ds-DNA antibodies were tested. In addition, the side effects and drug usage were observed during the patients’ treatment and follow-up. Results. Remissions in clinical symptoms such as facial rash, vasculitis, and proteinuria were noted in most patients. There are also evident reductions in SLEDAI, anti-ds-DNA antibodies, and GC dose and increases in C3 and C4 levels, with no pathogenic side effects during treatment and follow-up. Conclusions. T cell vaccination is helpful in alleviating and regulating systemic lupus erythematosus manifestation.